Investigation of Hypothermia and Hypoglycemia Complex in Newborn Lambs - Gök, Taşkın; Gül, Yusuf (My University, 2018)
The aim of this study was to investigate the complex of hypothermia and hypoglycemia occurring inthe first 3 days (especially in the first 5-12 hours) of the life of lambs.The material of the study consisted of twenty healthy (control group), twenty mildly hypothermicand ten severe hypothermic lambs. After the general clinical examination of all the lambs includedin the study (heart and respiratory rate, body temperature), blood samples were taken from V.Jugularis according to the procedure and serums were separated. The blood glucose level wasdetermined by a glucometer from the whole blood samples whereas total protein and albumin weredetermined in the serum by a refractometer.It was determined that the mean values of body temperature, respiration and heart frequencieswere 39.36±0.22oC, 55±5.79 pcs/min and 146.9±9.37 pcs/min in healthy lambs, 37.66±0.48oC,34.90±5.48 pcs/min and 72.40±10.15 pcs/min in mildly hypothermic lambs, and 36.49±0.34oC,20.00±4.52 pcs/min and 51.00±4.35 pcs/min in severely hypothermic lambs, respectively. It wasdetected that the mean values of glucose, albumin and total protein of the blood were103.20±30.07 mg/dL, 3.22±0.38 g/dL and 6.18±1.17 g/dL in healthy lambs, 55.25±13.29 mg/dL,3.02±0.36 g/dL and 4.91±1.11 g/dL in mildly hypothermic lambs, and 20.20±4.83 mg/dL, 2.53±0.42g/dL and 3.90±0.55 g/dL in severely hypothermic lambs, respectively.With regard to the mean values of the clinical (body temperature, respiration and heart frequencies)and biochemical (glucose, albumin, and total protein) parameters, the differences between allgroups were found to be significant (P<0.05).It was attempted to replace the glucose reserves and adjust the body temperature to the normallevel by administering colostrum via the feeding bottle or stomach tube or intraperitoneal glucoseinjection for the treatment of animals with neonatal hypothermia and hypoglycemia (mildhypothermia and severe hypothermia).All the lambs in the control group were alive while 25% of the lambs with mild hypothermia and70% of the lambs with severe hypothermia died.In conclusion, the early diagnosis and timely treatment of mild cases are important because of thehigh level of mortality in severely hypothermic-hypoglycemic cases.
Keywords: Veterinerlik